2022
DOI: 10.5435/jaaosglobal-d-22-00141
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Operative Time and Intraoperative Blood Volume Loss Between Stemless and Short‐stem Anatomic Total Shoulder Arthroplasty: A Single Institution's Experience

Abstract: Introduction: There has been increasing interest in the use of stemless humeral implants for total shoulder arthroplasty when compared with both short-stem (SS) and standard-length implants. Although evidence for decreased surgical time and blood loss exists for stemless versus standard-length stems, far less literature exists comparing these clinical parameters for stemless versus SS implants. Methods: A retrospective review of consecutive anatomic total shoulder arthroplasty (aTSA) cases conducted by a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Previous studies have demonstrated an average intraoperative blood loss of approximately 350 mL in TSA procedures. 20 , 21 When accounting for postoperative blood loss, the overall blood loss after TSA is approximately 850 mL. 21 Blood transfusions carry associated risks of allergic reaction, infection, cardiovascular dysfunction, and disease transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated an average intraoperative blood loss of approximately 350 mL in TSA procedures. 20 , 21 When accounting for postoperative blood loss, the overall blood loss after TSA is approximately 850 mL. 21 Blood transfusions carry associated risks of allergic reaction, infection, cardiovascular dysfunction, and disease transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Gruson et al showed reduced pain at the time of discharge after stemless with a VAS of 0 in 83 patients compared to 4 in the short stem cohort of 47 patient which was associated with a reduced length of stay in the hospital. 4 In a study of 203 stemless aTSAs, 354 short stem aTSAs and 1159 traditional length stem aTSAs, Labrum et al stratified postoperative pain scores by stem type. 11 The authors found no differences in postoperative pain between any cohort across all pain metrics recorded during the first 3 months postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to stemmed implants, stemless anatomic implants have similar implant longevity and PRO’s. 1 , 14 , 15 , 22 , 24 , 26 However, stemless implants have been shown to result in less intraoperative blood loss, 4 reduced surgical time, 4 , 5 a lower rate of intraoperative fractures, 28 and improved center of rotation restoration. 21 …”
mentioning
confidence: 99%
“…Unlike lower extremity surgery, tourniquets cannot be used for shoulder arthroscopic surgery. In comparison, the methods of reducing intraoperative bleeding mainly rely on controlled blood pressure reduction and plasma radiofrequency hemostasis, and a large amount of normal saline irrigation is required during the operation [ 3 , 4 ]. Swelling of the shoulder joint, more wound exudation, and subcutaneous blood stasis often occur after surgery.…”
Section: Introductionmentioning
confidence: 99%